The use of structures of modification as a possible measure of language growth among pupils of the University of the Philippines Elementary School - Nicolas, Rosita E. 1926- (College of Education, University of the Philippines Diliman, 1967)
This study looked into the use of modification structures in the themes of pupils in Grades II to VI of the UP Elementary School as a possible measure of language growth in an attempt to discover a relationship between the use of modification structures and the increase in grade level.